Reprogramming of fatty acid metabolism: a hidden force regulating the occurrence and progression of cholangiocarcinoma - Jianfeng Yang; Kaiyi Ruan; Zhaowei Chu; Xiang Wang; Ye Gu; Hangbin Jin; Xiaofeng Zhang; Qiang Liu; Jianfeng Yang (2025)
Abstract Cholangiocarcinoma (CCA) is a malignant tumor that originates from the bile duct epithelium and with a poor outcome due to lack of effective early diagnostic methods. Surgical resection is the preferred method for cure, but treatment options are limited for advanced diseases, such as distant metastatic or locally progressive tumors. Therefore, it is urgent to explore other new treatment methods. As modern living standards rise, the acceptance of high-fat, high-protein, and high-carbohydrate diets is growing among the public, and the resulting metabolic abnormalities are intimately linked to the initiation and spread of tumors. Metabolic reprogramming is a key mechanism in the process of tumor development and progression and is closely related to cancer cell proliferation, metastasis and drug resistance. Fatty acid (FA) metabolism, an integral component of cancer cell metabolism, can provide an energy source for cancer cells and participate in cell signaling, the regulation of the immune response and the maintenance of homeostasis of the internal environment, which are closely linked to the development and progression of CCA. Therefore, a better understanding of FA metabolism may provide promising strategies for early diagnosis, prognostic assessment and targeted therapy for CCA patients. In this paper, we review the effects of FA metabolism on CCA development and progression, summarize related mechanisms and the existing clinical applications of targeted lipid metabolism in CCA, and explore new targets for CCA metabolic therapy.